Improving the employment rates of people with disabilities through vocational education - Kostas G. Mavromaras; Cain Polidano (Institute for the Study of Labor (IZA), 2011)
During the 2001-8 period, the employment rate of people with a disability remained remarkably low in most western economies, hardly responding to better macroeconomic conditions and favourable anti-discrimination legislation and interventions. Continuing health and productivity improvements in the general population are leaving people with disabilities behind, unable to play their role and have their share in the increasing productive capacity of the economy. This paper combines dynamic panel econometric estimation with longitudinal data from Australia to show that vocational education has a considerable and long lasting positive effect on the employment participation and productivity of people with disabilities.
urn:nbn:de:101:1-201104133691
Keywords: J14; I19; I29; 330; employment; disabilities; productivity; vocational training; dynamic panel regression; Behinderte Arbeitskräfte; Berufsbildung; Behinderte; Berufliche Integration; Schätzung; Australien